Harnessing cutting edge technologies in combating procurement fraud - Tungkir, Fwangshak Samuel; Ugwu, Kelechi; Anya, Collins Uchechukwu (Journal of Commerce, Management, and Tourism Studies, 2025)
As deep-sea mining and marine mineral extraction enterprises expand into underexplored oceanic territories, the intricacy of these operations introduces multifaceted challenges. These include elevated operational costs, technical sophistication, increased susceptibility to fraudulent activities, workforce capacity gaps, as well as ethical and regulatory concerns. This study explores the role of cutting-edge technologies in mitigating procurement fraud within the marine mineral sector in North Central Nigeria. Specifically, it examines the impact of artificial intelligence adoption on enhancing the detection and prevention of procurement-related fraud. This research utilized a quantitative research method using a survey technique as an instrument for data collection. The study utilized the Tarro Yamane method to determine sample size. The study adopts a quantitative research method. The questionnaire was administered to a population of four hundred and eight (480) participants with in the North central, Niger State and Plateau State. Bowley proportional allocation method was used to determine an optimum number of questionnaires suitable for each stratum within the selected states, North Central, Niger State and Plateau State, Nigeria. The Pearson correlation result revealed that artificial intelligence positively influences procurement fraud detection in the deep-water mining industry. This result confirms a positive result with the value of (p .000, r = .990, N = 207). Managers are advised to deploy digital technologies to monitor and track marine mineral production, supply chain activities, and financial transactions of firms. This will help firms to enhance transparency, trust, decrease human errors, and improve data quality. This study advances trust-disruptive theory by connecting emerging technology and procurement using deep-seawater or marine mineral sectors. The study provides the deep-water mining industry and other organizations with new insight on how to proactively assess and manage procurement problems leading to the cost of adopting new technology and staff development and compliance demands.